Peranan Kantor Urusan Agama (KUA) Dalam Penguatan Ketahanan Keluarga di Kecamatan Tepus - Iin Sunny Atmaja; Andrie Irawan; Zainul Arifin; Ihab Habudin; Nur Mukhlis Zakaria; Syawal Rusmanto (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
This research is related to the role of KUA in the realization of family resilience (tahaga) in the life of the Muslim community in Tepus sub-district in Gunung Kidul Regency. The benefits can be felt in the mapping of external factors in family resilience that can affect life, including social conditions and community participation. Judging from its nature, this qualitative socio-juridical research includes descriptive research which intends to provide as accurate a data as possible about natural conditions in activities that show the role of KUA Tepus District in strengthening family resilience. The data were then obtained by participatory observation, in-depth interviews with informants from the KUA and office documentation on all matters relating to the object of research. The task of KUA Tepus District has supported its role in strengthening family resilience in the community related to religious, psychological and sociological resilience as well as the community's economy.